Nurses’ Knowledge Regarding Heart Failure Education Principles in Erbil Teaching Hospital - Bootan Hasan Ahmed; Sideeq Sadir Ali; Vian Afan Naqshbandi; Ribwar Arsalan Mohammed (Erbil Journal of Nursing and Midwifery, 2018)
Background and objective: Heart Failure is a major public health problem often associated with a decreased quality of life and high mortality rate. To optimize the quality of management and support patients to care for themselves in their own homes, they need to be well-educated about all aspects of the heart failure. This study aims to investigate nurses’ knowledge regarding the treatments that can be taught to heart failure patients to improve self-care. Methods: Cross-sectional study, 64 nurses out of 85 working at three public hospitals in Erbil City took part, the data was collected from 15th February to 15th March 2017 through interviews using a questionnaire schedule. The data was analyzed using Statistical Package for the Social Science (SPSS) program version 20. Results: Majority of the participants were young (87.6% within the range of 21-40), male (62.5%), and graduated with a technical diploma (60.9%). More than half of them (53.1%) have between 1–5 years of nursing experience, 50% of the nurses work in the Surgical Speciality Hospital - Cardiac Centre and 43.8% of them have general knowledge of Cardiac care. The majority of participants achieved a good knowledge score (70.3%). There was a significant association between level of knowledge of nurses working in the Surgical Speciality Hospital - Cardiac Centre and Rizgary Teaching Hospital, while few of them are in Hawler Teaching Hospital (53.3%, 26.7% and 20% respectively P <0.002). Conclusion: The study concluded that the nurses have good knowledge score, but still need continuous knowledge and practical training to educate patients regarding heart failure. High level of significance was found between the levels of knowledge and the working area.